Spatial and temporal variation of the fire regime in Mkuzi Game Reserve - Mulqueeny, Craig (My University, 2006)
Fire is a key determinant of savanna dynamics, and would thus have a major influence on the vegetation dynamics of Mkuzi Game Reserve. Given this logic, it is an important and commonly used management tool in this reserve. Its main uses in the reserve are for either removing moribund material or for reducing woody plant encroachment, both of which normally entail dry season burns. As a consequence, fire often results in a green flush of vegetation that is highly favoured by grazing herbivores. A further management goal is maintaining or improving biological diversity by promoting vegetation heterogeneity. Current policy prescribes this should be achieved through point-source ignitions rather than by block-burning, which was the earlier practice. This study explores spatial and temporal fire patterns at a landscape scale in Mkuzi Game Reserve using Geographic Information Systems (GIS). Much of our understanding of the dynamics of fire has previously been determined at a plot scale and scaling up of these insights to a landscape scale is problematic, hence this project aimed to contribute to our understanding of the dynamics of fire at a landscape scale. The study also specifically examined how the fire regime in the reserve has changed with a change in the burning philosophy and strategy, namely from block burning to the point source ignition (PSI) strategy, which began to be implemented in the mid-1980's. Fire frequency was related to both geological type and vegetation type. The fact that geology was related to fire frequency was not surprising because the relationship between geology and vegetation in the reserve has previously been established. The varying amount of herbaceous material per vegetation type apparently influenced fire frequency. Spatial variation in fire frequency was also positively related to rainfall variation over the reserve, while the total area burnt per annum was positively related to the preceding wet season rainfall, but not for years with a high dry season rainfall. The influence of rainfall on grass production and thus fuel load explained these relationships. In addition, there was some evidence of a carry over effect of rainfall where the previous wet season rainfall together with the preceding wet season rainfall influenced total annual area burnt, but this was only significant for years when dry season rainfall was low. Contrary to an expected negative influence, dry season rainfall had no effect on the total annual area burnt. Grazer biomass had a significant limiting effect on fire frequency over the reserve (spatially), most likely due to consumption of herbaceous ii material, but there was no relationship between grazer biomass and total annual area burnt (temporally). Dry season burns were significantly larger than wet season burns and can be attributed to the more favourable fuel condition during the dry season. Intense burns were also generally larger than the cooler burns, namely those rated as patchy/very patchy and clean. This was mainly attributed to a high fuel load which is critical for intense fires but also positively influences the spread of fire. The comparison of the block burning strategy and the point source ignition (PSI) strategy showed that fire frequency was greater during the PSI burning period than during the block burning period. The total area burnt per annum was greater during the PSI burning period than during the block burning period, but individual burn sizes were not significantly different between the two strategies. Evidence showed that individual burns that occurred during the PSI period had boundaries that were more irregular than those of block burns. Fires were most common during the dry season for both burning strategies, but the proportion of the burns that occurred during the dry season was greater for the PSI burning period than for the block burning period. Evidence also showed that a much greater emphasis was put on applying dry season prescribed burns during the PSI period than during the block burning period. A greater effort was also made during the PSI period to burn firebreaks, which were only implemented during the dry season. Arson fires (started deliberately or accidentally by neighbours) were more common during the block burning period than during the PSI period, while under both burning strategies, they were more common during the dry season than the wet season. There was no distinguishable difference in the burn intensity patterns between block and PSI burning, that is, the proportions of burns in the different burn intensity classes were not significantly different between the two burning strategies. Although the contribution of the individual fire barrier types showed some change with a change from block burning to a PSI strategy, the combined contribution of natural barriers did not increase, and that of management barriers did not decrease, as would have been expected. In addition, natural and management barriers were apparently of equivalent importance during both burning strategies.
Faculty of Science School of Animal,Plants and Enviromental Science 0204279a craigm.kznwildlife.com
Keywords: Fire; Fire Patterns; Fire Management; Savanna Ecology